Западноевропейские и западноазиатские варианты гаплогруппы R1b в украинских популяциях - Утевская, О.М.; Дибирова, Х.Д.; Чухряева, М.И.; Агджоян, А.Т.; Атраментова, Л.А.; Балановская, Е.В.; Балановский, О.П. (Фактори експериментальної еволюції організмів, 2015)
Aims. We studied the contribution of the West European and West Asian variants of Y-chromosomal haplogroup R1b into Ukrainian gene pool. Methods. The Y-STR profiles of R1b haplotypes with known variant affiliation were used to define the affiliation of Ukrainian haplotypes. Results. Locus DYS393 differentiates R1b-M269 haplotypes into West Asian (M269 (xL23), L23 (xM412), alleles 12 and lower) and West Eurpean (M412, alleles 13 and higher) with accuracy above 90 %. Ukrainian STR haplotypes were distributed between Asian and European parts of the median network in the ratio 1:2. The frequency distribution of DYS393 alleles in Ukrainians was intermediate between those of Asian and European populations. Conclusion. Our results indicate mixing of the different R1b lineages in the contact zone between Asia and Europe. The presence of Asian and European subhaplogroups R1b in Ukrainian populations is caused by the migratory flows from west and east.